Des hystériques en mouvement : d’une assignation à une libération des corps ? Engagement des médecins et discours thérapeutiques dans la seconde moitié du XIXe siècle en France - Grégory Quin; Anaïs Bohuon (Genre & Histoire)
Throughout the nineteenth century, a growing part of the French medical field focuses on this specific « pathology » called Hysteria. At that time, doctors are producing a rich literature especially fixed on female bodies, a big corpus which is also a great opportunity for the history we want to do: to analyse both the representations around female moving bodies and the influences of the biological theories and the epistemological transformations of medicine. Around hysteria, body movement and therapeutic efficiency allow a controlled “female body liberation”, but the socio-political frame – shared by doctors – still contributes to maintain women in their social and medical corset. Doctors’ commitment does contribute to reinforce the sexual dichotomy of the French society of the second half of the nineteenth century, and in the same dynamic they contribute to strengthen the connection made between motherhood and femininity as a pillar from Bourgeois’ ethos. With our focalisation on hysteria, our ambition is to analyse in deep, at the border between medicine and pedagogy, discourses’ flow made for physical activities that can heal female bodies concerned by hysteria.